Scaling climate-smart innovations using the Gender Action Learning System (GALS) Tool - Enokenwa Baa, Ojongetakah (International Water Management Institute, 2025)
Climate variability and agricultural soil degradation continue to leave smallholder farmers vulnerable to low yields and food insecurity. While sustainable climate-smart farming practices, such as Conservation Agriculture (CA), are recognized for their potential to enhance productivity, their adoption is often hampered by socio-cultural barriers. Specifically, women and youth face limitations in resource access and ownership, agency, decision-making power, and participation in agricultural planning. The Gender Action Learning System (GALS) addresses this gap. GALS is a transformative, community-led empowerment methodology that uses principles of inclusion to improve the income, food, and nutrition security of vulnerable people in a gender-equitable way. This strategic approach builds a connection between formal and informal institutions to transform existing exclusionary practices. Structured into four main components, the GALS tool provides the conceptual foundation for operationalizing key challenges related to participation, equitable distribution of resources, voice, and agency—all crucial for the adoption and scaling of innovations while creating safe spaces for decision-making at the household and community level.